Effect of Holostemma annularis on the progression of diabetes induced by a high fructose diet in rats and in diabetic C57BL/6J ob/ob mice - Ibrahim M (Diabetes, Metabolic Syndrome and Obesity, 2010)
Sudharshan Reddy D1, Muchandi IS2, Srinivasa Rao A3, Pradeep HA1, Ravi Kumar K1, Srinivasa Rao M1, Mohammed Ibrahim11Nizam Institute of Pharmacy, Hyderabad, Andhra Pradesh, India; 2HSK College of Pharmacy, Bagalkot, Karnataka, India; 3Bhaskar College of Pharmacy, Hyderabad, Andhra Pradesh, IndiaAbstract: The roots of Holostemma annularis K. Schum (Asclepiadacae) are used in traditional medicine to treat diabetes. This medicinal plant, widely used in more than 34 ayurvedic preparations, was evaluated in a high fructose diet in induced insulin resistance and in C57BL/6J ob/ob diabetic mice for its antidiabetic activity. Graded doses of both chloroform and methanolic extracts of the roots of H. annularis were administered to normal and experimental diabetic rats for 21 days. Serum glucose, triglycerides, cholesterol levels and total protein in urine were analyzed. Significant results were observed in the estimated parameters. These data justify the use of the plant in the treatment of diabetes mellitus and is a potential source for the isolation of new active agents for diabetes mellitus.Keywords: Holostemma annularis, high fructose diet, antihyperglycemic, C57BL/6J ob/ob mice